Analysis of Nursing Care for Elderly People Experiencing Isolation/Depression with Anxiety Problems Using Dhikr Relaxation at Sentra Gau Mabaji Gowa - fitriani, aidah (Journal of Community Engagement in Nursing, 2024)
Background Isolation/Depression syndrome in the elderly with anxiety/depression problems can affect their life because it causes loss of appetite, dizziness, high blood pressure, irritability, sadness, difficulty concentrating, and unable to sleep. One type of therapy that can reduce anxiety is dhikr relaxation. The purpose To analyze nursing care for the elderly experiencing isolation/depression with anxiety problems using dhikr intervention at the Gau Mabaji Gowa Sentra in 2022. Methods Metodh used is a descriptive approach with a case study method. The subjects used were individuals/patients who met the inclusion and exclusion criteria. The instruments used in this case study were the format of the nursing care process and Standard Operating Procedures (SOP) in conducting dhikr therapy, studying depression scale measurements. Data analysis is presented textually with facts put in text form and explained narratively. Results Result of giving dhikr therapy were carried out for 5 days from 27 September to 03 October 2022 at Sentra Gau Mabaji Gowa and the results showed that the patient’s depression level decreased from 13 to 7. Conclusions Conclusion based on the results of the case evaluation stated that dhikr therapy was effective in reducing depression levels. Keywords: Isolation/Depression, Anxiety, dhikr therapy